Research in the History of Philosophy of Nature and the History of Science - Mączka, Janusz; Skoczny, Włodzimierz; Koleżyński, Andrzej; Polak, Paweł; Karolczak, Maria; Sieńko, Dorota; Dziekan, Małgorzata (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
This is a review of research conducted by the Center for Interdisciplinary Studies and the Copernicus Center for Interdisciplinary Studies in the field of the history of philosophy of nature and the history of philosophy of science in Poland in the inter-war period. In spite of the domination of positivistic philosophy that tended to ignore philosophy of nature, this kind of philosophizing was quite popular in Poland. The review begins with a summary of works related to the history of science, and then deals, in some detail, with works on the theory of evolution and the theory of relativity, especially with their philosophical aspects. The remaining part of the review is devoted to the principal personalities of that period, namely: Władysław Heinrich, Władysław Natanson, Tadeusz Grabowski, Marian Smoluchowski, Zygmunt Zawirski and Joachim Metallmann.